Sources of trust in the healthcare context. A multilevel relationship with work engagement and organisational outcomes - Olvera, Juana; Acosta-Antognoni, Hedy; Llorens, Susana; Salanova, Marisa (Frontiers in Psychology, 2024)
The present study analysed the mediating role of interactional justice and horizontal trust between transformational leadership and organisational outcomes (i.e., job performance and service quality) at the work team level and the cross-level relationship of team horizontal trust with job performance at the individual level, controlling for work engagement. The sample corresponds to 1.638 workers grouped into 109 work teams belonging to 28 hospitals in Spain. First, Structural Equation Modelling analysis revealed that, as expected, at the team level, interactional justice and horizontal trust mediate positive and significantly the relationship between transformational leadership and organisational outcomes (i.e., job performance and service quality). Secondly, the results of the Linear Hierarchical Models showed a positive relationship between work engagement and individual level performance. Finally, the multilevel analysis revealed that there is no cross-level relationship between horizontal trust at the team level and individual performance controlled by work engagement.